Entomological parameters and population structure at a microgeographic scale of the main Colombian malaria vectors Anopheles albimanus and Anopheles nuneztovari (2023)
Population subdivision among several neotropical malaria vectors has been widely evaluated; however, few studies have analyzed population variation at a microgeographic scale, wherein local environmental variables may lead to population differentiation. The aim of the present study was to evaluate the genetic and geometric morphometric structure of Anopheles nuneztovari and Anopheles albimanus in endemic localities of northwestern Colombia. Genetic and phenetic structures were evaluated using microsatellites markers and wing geometric morphometrics, respectively. In addition, entomological indices of importance in transmission were calculated. Results showed that the main biting peaks of Anopheles nuneztovari were between 20:00 and 22:00, whereas Anopheles albimanus exhibited more variation in biting times among localities. Infection in An. nuneztovari by Plasmodium spp. (IR: 4.35%) and the annual entomological inoculation rate (30.31), indicated high vector exposure and local transmission risk. We did not detect Plasmodium-infected An. albimanus in this study. In general, low genetic and phenetic subdivision among the populations of both vectors was detected using a combination of phenotypic, genetic and environmental data. The results indicated high regional gene flow, although local environmental characteristics may be influencing the wing conformation differentiation and behavioral variation observed in An. albimanus. Furthermore, the population subdivision detected by microsatellite markers for both species by Bayesian genetic analysis provides a more accurate picture of the current genetic structure in comparison to previous studies. Finally, the biting behavior variation observed for both vectors among localities suggests the need for continuous malaria vector surveys covering the endemic region to implement the most effective integrated local control interventions